Pleasure and the arts : enjoying literature, painting, and music - Butler, Christopher, 1940- (Oxford University Press, 2005)
How do the arts give us pleasure? Covering a very wide range of artistic works, from Auden to David Lynch, Rembrandt to Edward Weston, and Richard Strauss to Keith Jarrett, Butler offers us an explanation of our enjoyable emotional engagements with literature, music, and painting. Pleasurable in its own right, Pleasure and the Arts presents a sparkling explanation of the enduring interest of artistic expression. - ;How do the arts give us pleasure? Covering a very wide range of artistic works, from Auden to David Lynch, Rembrandt to Edward Weston, and Richard Strauss to Keith Jarrett, Pleasure.